Gradišćanskohrvatski rukopisni vinogradarski zakonik iz 1769. godine - Dudás, Előd (SlavVaria, 2026)
Burgenland Croatian manuscript winegrowing code from 1769. The paper presents the Burgenland Croatian manuscript winegrowing code from 1769, which contains all the rights of winegrowers in Hrvatski Židan (Hung. Horvátzsidány) and Prisika (Hung. Peresznye). This manuscript is the only example of a secular text among religious texts in the 18th century. Some general information is given about the Burgenland Croats and their origin and settlement in western Hungary. The main part of the paper includes a linguistic analysis of the text at the phonological, morphological and lexical levels. Morphological features are presented according to variable and invariable parts of speech, and the lexical analysis includes a presentation of Čakavisms, Germanisms, Hungarianisms and Romanisms, as well as loan translations.